097 Valosin Containing Protein (VCP) and Myofibrillar Myopathies (MFM) genes' mutations are not associated with sporadic Inclusion Body Myositis (sIBM). Issue 3 (9th February 2012) - Machado, P; Hudson, J; Miller, A; Morrow, J; Parton, M; Bushby, K; Hanna, M
Abstract : Background: Inclusion body myopathy with dementia and Paget disease of bone (IBMPFD) and myofibrillar myopathies (MFM) are genetically determined myopathies that can mimic sporadic Inclusion Body Myositis (sIBM), especially if the disease phenotype is incomplete (eg, skeletal muscle involvement only), if there is no family history (either because a mutation arises in the germ line or because the disease in the parents was unrecognised) and if the histological features overlap with those of sIBM. It is therefore possible that some sIBM cases may be caused by undetected mutations in the IBMPFD and MFM causative genes. Objective: To investigate the association of sIBM with mutations in the IBMPFD and MFM causative genes. Methods: Twenty-nine patients with sIBM (meeting diagnostic criteria for definite or probable sIBM according to Griggs) were screened for mutations in the following genes: valosin containing protein (VCP), Desmin (DES), Myotilin (MYOT) and Crystallin alpha-B (CRYAB). Results: No pathogenic mutations in the VCP, DES, MYOT and CRYAB genes were detected in this group of sIBM patients. Conclusion: This study provides evidence that common mutations in the VCP, DES, MYOT and CRYAB genes are not associated with the development of sIBM. Our results support current clinical practice in patients with sIBM, which are not usually screened for mutations in these genes, unless there the history or biopsy findings suggest a genetically determined myopathy.